Advertisement Remove all ads

Factorise: X2 + 6x + 9 - 4y2 - Mathematics

Advertisement Remove all ads
Advertisement Remove all ads
Advertisement Remove all ads
Sum

factorise:  x2 + 6x + 9 - 4y

Advertisement Remove all ads

Solution

x2 + 6x + 9 - 4y

= (x)2 + 2 × x × 3 + (3)2 - (2y)2

             ...[(a + b)2 = a2 + 2ab + b2]
             ...[a2 - b2 = (a + b)(a - b)]   

= (x + 3)2 - (2y)2

= (x + 3 + 2y) (x + 3 - 2y)

= (x + 2y + 3) (x - 2y + 3)

Concept: Factorisation by Difference of Two Squares
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 13 Factorisation
Exercise 13 (C) | Q 20 | Page 159
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×